Notes from the fortune-telling parrot : Islam and the struggle for religious Ppuralism in Pakistan - Pinault, David (Comparative Islamic studies., 2008)
This book explores the richness of Pakistan?s religious landscape and utilizes a number of topics in an investigation of how Islamist politicians seek to eradicate sectarian diversity and repress localized forms of Muslim folk practices in the name of a standardized, uniform and globalized version of Islam. The book examines forms of resistance to this Islamist globalization to repeal Pakistan?s notorious blasphemy law and assert the worth of religious pluralism.